Sosialisasi Empat Pilar Literasi Digital di SMP Islam Terpadu An Nizomiyah Jakarta - Dwi Kartikawati; Nurhasanah Nurhasanah (Jurnal Syntax Admiration, 2024)
The purpose of this community service activity is to provide socialization of 4 (four) pillars of digital literacy to be smart in the digital space at SMP Islam An Nizomiyah Jakarta. Activities are focused on SMP An Nizomiyah Jakarta because this school has never been introduced to digital literacy even though most of the junior high school students in this school use digital media for various things which of course are at risk of being negatively affected if not equipped with digital literacy knowledge. Digital literacy is an indispensable skill for students to master as future generations of leaders. Therefore, education has a big role in supporting the mastery of students' digital media literacy skills. Digital media literacy occurs if a person can process various information, understand information, and communicate effectively with others in various forms of media. Digital media literacy is a life skill that not only involves the skills to use technology and information devices but also individual skills to socialize and have a critical thinking attitude as one of the digital competencies.